Differentiated Learning in Padang City Public Elementary Schools on IPAS Learning in the Merdeka Curriculum - Syofiani, Syofiani; Edni Juliani, Nilam; Pebriyenni, Pebriyenni; Zahra, Zahra; Afni, Nur (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2025)
The new independet curriculum allows students to show off their scientific talents in an environment free of stress, anxiety, and worry thanks to its relaxed and enjoyable learning style. Science learning, an invention of the independent curriculum, combines the scientific and social sciences. In order for children' minds to grow and their imaginations to flourish, science education is crucial. Aiming to foster children's creativity, independence, and psychological well-being, scientific education is methodically designed to facilitate learning via interaction, inspiration, entertainment, challenge, and active involvement. Furthermore, it is anticipated that youngsters can cultivate analytical, imaginative, and inquisitive thought processes. An attempt to tailor the educational experience to the unique requirements of each student is known as differentiated learning. At this time, differentiated learning is not widely used. Content, processes, products, and learning settings were all considered in the researchers' literature assessment. This literature study aims to accomplish three goals: (1) define differentiated learning; (2) describe its principles and characteristics; and (3) examine its applications in scientific education. Books and scholarly papers form the basis of this literature evaluation. The analysis reveals that: (1) students' learning styles can be accommodated by combining differentiated approaches with various models that meet their needs, such as Problem Based Learning (PBL), Project Based Learning (PjBL), and others; (2) students find this approach more engaging and it can improve their learning outcomes; and (3) students' interests and learning styles can be met by using this approach in science learning.